The Pension System and its Financing as an Important Part of Public Finances in the Slovak Republic - Sika, Peter; VidovÃ¡, Jarmila (International Journal of Economics and Financial Issues, 2018)
Spread of the Slovak pension system to several pillars significantly increased the deficit of the predominantly ongoing pension system administered by the Social Insurance Fund. At the same time, the transformation costs have increased, which exacerbate the public finance deficit and the financial sustainability of the pension system, especially in the short term. The private pension system, which was built on a voluntary basis in the initial phase, gained a significant position in retirement provision as well as in popularity among citizens of the Slovak Republic thanks to mass promotion. Despite several unsuccessful government attempts to return citizens to a purely ongoing system due to the inefficiency of being a private pension savings scheme, the National Council of the Slovak Republic has come to weaken old-age pension savings through a set of measures. Keywords: Deficit of public finances, Sustainability of the pension system, Retirement pension savings, Retirement age JEL Classifications: G23, J45, J38.